1995
DOI: 10.1073/pnas.92.26.12151
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase D signaling is essential for meiosis.

Abstract: Phospholipid metabolism plays an important role in cellular regulation by

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
214
2

Year Published

1996
1996
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 201 publications
(219 citation statements)
references
References 33 publications
3
214
2
Order By: Relevance
“…3), demonstrating that yeast contains at least two independent phospholipases D. With yeast PtdCho or POPC as the substrate, PLD activity was low in membrane fractions from the wild type cells incubated in the presence of EDTA and disappeared in membranes from pldl mutants. Cleavage of NBD-PtdCho by Pldlp is strongly stimulated by PIP2 (4 mol%), which is in accordance with previous reports [9,11]. Ca-PLD is not affected by PIP2 (Fig.…”
Section: Phospholipase D Activity In Pldl Mutantssupporting
confidence: 93%
See 4 more Smart Citations
“…3), demonstrating that yeast contains at least two independent phospholipases D. With yeast PtdCho or POPC as the substrate, PLD activity was low in membrane fractions from the wild type cells incubated in the presence of EDTA and disappeared in membranes from pldl mutants. Cleavage of NBD-PtdCho by Pldlp is strongly stimulated by PIP2 (4 mol%), which is in accordance with previous reports [9,11]. Ca-PLD is not affected by PIP2 (Fig.…”
Section: Phospholipase D Activity In Pldl Mutantssupporting
confidence: 93%
“…Colocalization of both phospholipases D in the plasma membrane suggests that these enzymes may be involved in signal transduction pathways signalling external stimuli. However, for Pldlp/ Spol4p this appears unlikely [9], since cells lacking Spol4p undergo the first steps of meiosis [14]. Since wild type cells are insensitive to external stimuli after having decided for meiosis, it was suggested that Pldlp is activated rather by an, as yet unidentified, internal event.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations